2008
DOI: 10.1016/j.pain.2007.09.010
|View full text |Cite
|
Sign up to set email alerts
|

Self-efficacy for managing pain, symptoms, and function in patients with lung cancer and their informal caregivers: Associations with symptoms and distress

Abstract: This study examined self-efficacy for managing pain, symptoms, and function in patients with lung cancer and their caregivers, and associations between self-efficacy and patient and caregiver adjustment. 152 patients with early stage lung cancer completed measures of self-efficacy, pain, fatigue, quality of life, depression, and anxiety. Their caregivers completed a measure assessing their self-efficacy for helping the patient manage symptoms and measures of psychological distress and caregiver strain. Analyse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

17
187
3
9

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 235 publications
(216 citation statements)
references
References 30 publications
17
187
3
9
Order By: Relevance
“…This finding was surprising given that several chronic pain researchers have demonstrated that selfefficacy significantly predicted pain intensity (Porter et al, 2008;Woby et al, 2007) and, further, that catastrophizing is negatively correlated with self-efficacy appraisals for controlling or decreasing pain (Desrochers et al, 2009;Geisser, Robinson, & Riley, 1999). However, Desrochers et al (2009Desrochers et al ( , 2010 have reported some inconsistent results regarding the role of selfMediation in Couples with PVD 24 efficacy in PVD pain.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…This finding was surprising given that several chronic pain researchers have demonstrated that selfefficacy significantly predicted pain intensity (Porter et al, 2008;Woby et al, 2007) and, further, that catastrophizing is negatively correlated with self-efficacy appraisals for controlling or decreasing pain (Desrochers et al, 2009;Geisser, Robinson, & Riley, 1999). However, Desrochers et al (2009Desrochers et al ( , 2010 have reported some inconsistent results regarding the role of selfMediation in Couples with PVD 24 efficacy in PVD pain.…”
Section: Discussionmentioning
confidence: 95%
“…Studies have demonstrated associations between participant-and partner-perceived self-efficacy and participant pain as well as the psychosocial functioning of both members of the dyad (Porter et al, 2002(Porter et al, , 2008. These results underscore the potential for partner-related cognitive variables to influence outcomes in people with pain.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…In other words, depressed and anxious inpatients may feel less well for a given pathophysiology-ie, they may have less disease than the average inpatient with a similar illness. Furthermore, the challenges some clinicians may encounter while treating patients with mental disorders, with perhaps lower self-efficacy for managing pain and other symptoms, and less resiliency in maintaining function [30], might contribute to a higher rate of discharge to rehabilitation facilities. In line with our findings, a recent study found that dementia was the only independent risk factors for 90-day postoperative mortality after TKA [5].…”
Section: Discussionmentioning
confidence: 99%
“…According to a recent literature review on telehealth interventions [80], a precise structure linking all aspects of the intervention or of the outcomes is rarely found and most of the projects lack a theoretical framework. Nevertheless, even in the general literature (beyond telehealth interventions) there are unfortunately only few studies which assess correlations or mediate effects between different constructs (e.g., Quality of Life, depression, self-efficacy) which are related to caregiver's needs (e.g., information provision, social support, self-management education etc) [81,82].…”
Section: Discussionmentioning
confidence: 99%